Integrating Religious Moderation into the Merdeka Curriculum: A Strategic Educational Management Perspective - Putri Mulyaningsih Pou; Kasim Yahiji (Al-Qalam Institue, 2026)
This study aims to examine the internalization of religious moderation values within the development of the Merdeka Curriculum from an educational management perspective. Using a qualitative library research approach, data were collected through the analysis of relevant academic literature, including peer-reviewed journals, scholarly books, and credible online sources related to religious moderation, curriculum reform, and educational management. The findings reveal that the internalization of religious moderation is realized through a systematic value transformation process encompassing moral knowledge, moral feeling, and moral action, which are integrated into curriculum planning, instructional implementation, and learning evaluation. From an educational management dimension, effective internalization is supported by strategic curriculum management, alignment of learning objectives with character education, and value-based pedagogical governance. These results indicate that the successful integration of religious moderation within the Merdeka Curriculum requires coherent management practices that connect curriculum design, teaching strategies, and institutional values. This study implies that educational leaders and curriculum developers should prioritize value-oriented management frameworks to ensure the sustainable implementation of religious moderation within contemporary curriculum reforms.